2004
DOI: 10.1158/0008-5472.can-03-3425
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana Use and Risk of Oral Squamous Cell Carcinoma

Abstract: Previous laboratory investigations, case reports, and a hospital-based case-control study have suggested that marijuana use may be a risk factor for squamous cell head and neck cancer. We conducted a populationbased case-control study to determine whether marijuana use is associated with the development of oral squamous cell carcinoma (OSCC). Case subjects (n ‫؍‬ 407) were 18 -65-year-old residents of three counties in western Washington State who were newly diagnosed with OSCC from 1985 through 1995. Control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 31 publications
4
81
0
2
Order By: Relevance
“…However, epidemiological studies performed to date have not indicated that marijuana use increased risk for HNSCC. No association of marijuana use with oral cancers was observed in a California cohort study, 85 in a case-control study restricted to those under the age of 45,82,83 or in a population-based study in the U.S. 86 A single study in New York State reported elevated odds of oral cancer (OR 2.6, 95% CI, 1.1-6.6) among ever users of marijuana, after adjustment for age, sex, race, education, alcohol use and pack-years of tobacco use. 87 Risk also increased directly with duration and frequency of use.…”
Section: Marijuana Usementioning
confidence: 87%
See 1 more Smart Citation
“…However, epidemiological studies performed to date have not indicated that marijuana use increased risk for HNSCC. No association of marijuana use with oral cancers was observed in a California cohort study, 85 in a case-control study restricted to those under the age of 45,82,83 or in a population-based study in the U.S. 86 A single study in New York State reported elevated odds of oral cancer (OR 2.6, 95% CI, 1.1-6.6) among ever users of marijuana, after adjustment for age, sex, race, education, alcohol use and pack-years of tobacco use. 87 Risk also increased directly with duration and frequency of use.…”
Section: Marijuana Usementioning
confidence: 87%
“…87 These odds were likely inflated by the use of a control population of blood donors with half the expected frequency of marijuana use than reported in the general population. 86,88 In the majority of studies, assessment of risk was limited to ever versus never use of marijuana, and therefore risks associated with heavy use would likely be attenuated by the occasional user. Study power was also limited by small numbers of marijuana users, such that small elevations in risk that nevertheless may be important because of the high prevalence of marijuana use may not be measured.…”
Section: Marijuana Usementioning
confidence: 99%
“…Another study conducted in Washington State among 407 cases of oral SCC compared with controls recruited by randomdigit dialing found no association between marijuana use and risk of oral SCC. 32 The study was not limited to younger patients. However, age was one of the covariates included in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff for marijuana use may have been too low for cancer risk to be detected, and confounding by life-style risk factors could not be ruled out for the cervical and prostate cancer findings. The 14 case-control studies included 4 studies of head and neck cancers (5)(6)(7)(8), 2 studies of lung cancer (9,10), 2 studies of non-Hodgkin's lymphoma (11,12), 1 study of anal cancer (13), 1 study of penile cancer (14), 1 study of bladder cancer (15), and several studies of childhood cancers with assessment of parental exposures (16)(17)(18)(19). In a hospital-based study, Zhang et al (8) reported an association of marijuana use with head and neck cancers, with dose-response relations observed for both frequency and duration of use.…”
Section: Introductionmentioning
confidence: 99%